A study to observe the effects of physiotherapy with and without manual therapy in the management postural neck pain: a randomized control trial - Rubab Jawed; Muhammad Fareed Nasir; Nabeel Naeem Baig; Maryam Younus; Ayesha Arshad; Aisha Tahir (Journal of the Pakistan Medical Association, 2020)
A comparative follow up study of transabdominal preperitoneal mesh repair in inguinal hernias with or without mesh fixation